Young Women's Body Attitudes and Sexual Satisfaction: Examining Dehumanization and Communication as Serial Multiple Mediators. (June 2021) - Holland, Kathryn J.; Silver, Kristin E.; Cipriano, Allison E.; Brock, Rebecca L.
Women's bodies are frequent sites of stigmatization. The internalization of negative attitudes toward the body can have negative implications for women's sexual wellbeing. In the current study, we examined the relationships between young women's internalization of body stigma—including body shape, genitals, and menstrual periods—and sexual satisfaction. Additionally, we tested two mechanisms that may mediate the relationship between body attitudes and sexual satisfaction: dehumanization (i.e., feelings of a loss of autonomy and subjectivity) and communication with a sexual partner (e.g., expressing needs and desires). We collected and analyzed survey data from 569 undergraduate women. We tested serial mediation models, such that more negative body attitudes would predict greater feelings of dehumanization, and more dehumanization would predict less comfort communicating with a sexual partner, and less comfort communicating would then predict decreased sexual satisfaction. We found support for serial mediation, which suggests that the links between body attitudes and sexual satisfaction may be partially explained by feelings of dehumanization and communication with a sexual partner. Our findings identify opportunities for intervention in practice and policy, and further clarify the ways that sociocultural stigma surrounding women's bodies extends beyond the body—affecting women's feelings of power, relationships, and sexual lives. Online slides for instructors who want to use this article for teaching are available on PWQ's website athttp://journals.sagepub.com/doi/suppl/10.1177/0361684321994295